How to mix colors - Martin i Roig, Gabriel 1970- (Pocket art guides, 2014)
Overview: Art students and amateur painters alike will find advice and instruction in Barron's popular Pocket Art Guides series. Each title focuses on a specific aspect of painting or drawing, and includes tips that even experienced professionals will find helpful. These information-packed books are handy artists' companions for the reference shelf, but are also small enough to carry along with art supplies on field trips. How to Mix Colors explores the fundamentals of choosing and mixing colors as it applies to watercolors, acrylics, and oils. Includes captioned color illustrations and notes on how famous artists solved specific problems.